ANALISE DA COMPOSIÇÃO CORPORAL VIA MODELO DE REGRESSÃO BETA - PETTERLE, Ricardo Rasmussen; JONASSON, Thaísa Hoffmann; NASCIMENTO, Adriana Regina; BOGUSZEWSKI, Cézar Luiz; BORBA, Victória Zeghbi Cochenski (Brazilian Journal of Biometrics, 2018)
Population aging is a social reality. With advancing age come changes in body composition, such as increased weight, fat mass and reduced bone mass and lean. Body composition is dened as the ratio between the dierent components of the body, being expressed by percentages of fat, lean and bone mass. Its analysis is important to determine the components of the body aiding in weight loss programs and fitness. In addition, its review is an important mechanism for detection and prevention of some chronic diseases. The main objective of this paper is to analyze and investigate the relationship of body composition with age, gender, level of physical activity (IPAQ) and body mass index (BMI) of healthy individuals evaluated in the Endocrinology and Metabolism Department, at the Clinical Hospital of the Federal University of Paraná. As the percentage of fat, lean and bone masses belong to the unit interval (0,1) assumed Beta distribution for each of them, making use of the Beta regression model available in betareg software package R. The results showed that body composition of men and women was different. With advancing age there was an increase in body fat percentage and reduction in the percentage of lean and bone mass, both men and women. The level of physical activity, estimated by the IPAQ, proved to be a determining factor in body composition, such that active individuals had higher percentage of lean mass and a lower percentage of body fat, however, for the bone mass percentage, the IPAQ was not relevant.